From node to network: weaving a global perspective on efficacy and costs of non-pharmaceutical interventions - Chong Xu; Sameer Kumar; Muer Yang; Nidhi Ghildayal; Charu Chandra (Scientific Reports)
Abstract Non-pharmaceutical intervention (NPI) policies, ranging from mild measures to total isolation, were implemented worldwide during the COVID-19 pandemic. We adopt a systematic approach to guide policymakers in deploying NPI policies to mitigate the pandemic’s effects while balancing their social and economic impacts. Our results show that each NPI has an optimal duration, beyond which its effectiveness plateaus. Stricter policies require longer durations, and when sustained for the optimal period, earlier implementation is more effective. However, when this duration is unattainable, timing becomes critical, as both early and late implementation reduce efficacy. Stringent policies with insufficient durations may perform worse than less restrictive measures applied over the same period, and an NPI policy aimed at minimizing overall healthcare burden under a fixed policy duration may significantly intensify peak-time strains. Finally, as the virus becomes more transmissible and less lethal, the effectiveness gap between stringent and less restrictive policies narrows, with targeted interventions for vulnerable groups outperforming universal strict measures.